International Perspectives on Teaching the Four Skills in ELT Listening, Speaking, Reading, Writing (International Perspectives on English Language Teaching, 2018)
This book offers a range of perspectives and insights from around the world on the teaching and learning of listening, speaking, reading and writing. It brings together contributors from across six continents, who analyse a wide range of teaching and learning contexts, including primary, secondary, tertiary, private, and adult ESL/EFL classes. In doing so, they provide locally relevant accounts that nonetheless resonate with other contexts and wider concerns. This informative and practical edited collection will appeal to students and scholars who are interested in the four building blocks of language learning, as well as language education and teacher education. Anne Burns is Professor of TESOL at the University of New South Wales, Australia, and Professor Emerita, at Aston University, UK. She has published extensively on teaching speaking, action research and language teacher education. Joseph Siegel is Senior Lecturer in the School of Humanities, Education and Social Science at Örebro University, Sweden. His research interests include action research, listening pedagogy, contextual education comparisons and pragmatic interaction. .